Long-term development of mechanical properties of concrete with different water to cement ratio and internal curing ability (Fracture and Structural Integrity, 2024)
Concretes with water to cement (or binder) ratios of 0.50. 0.40, 0.30 and 0.20 were prepared and long-term mechanical properties were measured. Porous light-weight aggregates (LWA) in dosages of 10 % and 20 % were used for self-curing (internal curing) as a partial replacement of fine aggregates for some concrete types. Two environmental conditions were studied i.e., one under water and the other in foil, which prevents the extensive water exchange with the environment.Measured strengths at the ages of 28, 91, 365 and 720 days show  higher values for the specimens covered in foil than for the specimens stored in water. On the other hand, the presence of LWAs reduces the compressive strength and bending strength of concrete with w/c = 0.30 at the age of 28 days of curing. The tests performed at the ages of 91 days and 1 year show higher flexural strengths than those of specimens cured in foil than those cured in water and those with internal curing.
Keywords: bending strength; compressive strength; concrete; internal curing; water to cement ratio